Práticas educativas dos ritos de iniciação: um estudo comparado nas religiões monoteístas - Cruz, Josilene Silva da (2016)
In an attempt to present the relevance of Religious Education in the educational field and the relation of the universe of symbols in religion, we have made in this study the description of the initiation rites within the three monotheistic religions: Judaism, Christianity and Islam. In order to present a new proposal of teaching to practice the teaching of religious education, by comparing religions, we seek to identify the educational practices of the three selected rites: circumcision, baptism and shahada. The analysis was made by descriptive and bibliographic research of qualitative approach associated to participant observation. The methodology based on the comparative study of religions, phenomenology by Mircea Eliade. Our aim was to analyze the symbolic actions and the educational practice present in the initiation rites of the monotheistic religions considering their relevance and propose an epistemological and methodological conception to be practiced in Religious Education. In this study, we realized that although it being a theoretical research, the ritualistic practice can be used as a practical-didactic resource for teachers of Religious Education.